UJARAN KEBENCIAN NETIZEN INDONESIA DALAM KOLOM KOMENTAR INSTAGRAM OFFICIAL @MANCHESTERUNITED - Zetta Prahastuti; Yuyun Ulandari (Parataksis: Jurnal Bahasa, Sastra, dan Pembelajaran Bahasa Indonesia, 2024)
Hate speech on social media has become a serious concern, especially when it involves renowned football clubs like Manchester United. Through the analysis of illocutionary speech acts, this study explores Indonesian netizens' comments on Manchester United's official Instagram account in April 2024, expressing disappointment towards the club's performance. This research employs a descriptive qualitative method. Data collection involves observation and recording techniques, focusing on comments containing hate speech on the Instagram account @manchesterunited. Data analysis includes identifying illocutionary acts containing hate speech in each sentence within the Instagram comments. The aim of this research is to analyze Indonesian netizens' hate speech in the official Instagram comments section of Manchester United. This is done by identifying and classifying illocutionary speech acts within the comments using a forensic linguistic perspective. The analysis reveals that most comments contain elements of negative expression, insults, threats, and derogatory subjective evaluations. Dominant expressive speech acts reflect subjective evaluations and negative emotional expressions towards the club. Some comments also fall into the category of declarative speech acts, where speakers express bad hopes or desires towards the club. This study highlights the importance of awareness regarding the negative impact of hate speech on social media and the need for action to address and prevent its spread, not only in sports contexts but also in building a safer and more civilized online environment for all users.